Increasing the Tourists' Revisit Intention by Paying Attention to Tourist Satisfaction at The Gong Cave Pacitan Tourist Destination - Sulih Wahyudiono; Soerjanto , (Majalah Ilmiah Bijak, 2022)
This study explores empirical evidence of the relationship between tourist attractions and service quality and the revisit intention to Gong Cave Pacitan Tourist Destination by considering the mediation effect of tourist satisfaction. A total of 155 tourists who visited Gong Cave Tourism Object voluntarily at least twice participated in this study. Smart PLS 3.0 software is used to perform modelling of Least Squares Partial structure equations and hypothesis testing. The results show that tourist attractions and service quality do not affect tourists' revisit intention. Tourist satisfaction significantly and positively impacted the revisit intention. Tourist attractions do not affect tourist satisfaction. The service quality significantly and positively impacts tourist satisfaction. Tourist satisfaction cannot mediate the relationship between tourist attractions and tourist revisit intention. Tourist satisfaction is a variable that can mediate the relationship between service quality and tourist revisit intention.